Cryoballoon vs. radiofrequency lesions as detected by late-enhancement cardiac magnetic resonance after ablation of paroxysmal atrial fibrillation: a case–control study. Issue 3 (10th December 2019) - Alarcón, Francisco; Cabanelas, Nuno; Izquierdo, Marc; Benito, Eva; Figueras i Ventura, Rosa; Guasch, Eduard; Prat-Gonzalez, Susana; Perea, Rosario Jesus; Borràs, Roger; Trotta, Omar; Arbelo, Elena; Tolosana, José Maria; et al.
Abstract: Aims: Cryoballoon (CB) ablation has emerged as a reliable modality to isolate pulmonary veins (PVs) in atrial fibrillation. Ablation lesions and the long-term effects of energy delivery can be assessed by delayed-enhancement cardiac magnetic resonance (DE-CMR). The aim of the study was to compare the number, extension, and localization of gaps in CB and radiofrequency (RF) techniques in pulmonary vein isolation (PVI). Methods and results: Consecutive patients submitted to PVI with CB in whom DE-CMR images were available ( n  = 30) were matched (1:1) to patients who underwent PVI with RF ( n  = 30), considering age, sex, hypertension, and diabetes. Delayed-enhancement cardiac magnetic resonance was obtained at 3 months post-procedure, and images were processed to assess the mean number of gaps around PV ostia, their localization, and the normalized gap length (NGL), calculated as the difference between total gap length and total PV perimeter. Patients were followed up for 12 months. The CB and RF procedures did not differ in the mean number of gaps per patient (4.40 vs. 5.13 gaps, respectively; P  = 0.21) nor NGL (0.35 vs. 0.32, P  = 0.59). For both techniques, a higher mean number of gaps were detected in right vs. left PVs (3.18 vs. 1.58, respectively; P  = 0.01). The incidence of recurrences did not differ between techniques (odds ratio 1.87, 95% confidence interval 0.66–4.97; P  = 0.29). Conclusion: Location and extension of ablation gaps in PVI did not differ between CB and RF groups in DE-CMR image analysis.